Travel of Bonpo Gods from the Eurasian Borderlands to the Tibetan Culture Area and the Borderlands of North-east India - M.N. Rajesh (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2018)
Abstract Popular writing has brought about an image of Hindu deities that are seen as a part of Hinduism only and Hinduism is also seen as a religion of the Indian subcontinent. While this may be largely true in many cases, it forces us to look at Hinduism in very Semitic terms as a closed religion. On the contrary we see that there was a considerable travel of gods and goddesses from other religions into Hinduism and vice versa. And thus negates the idea of Hinduism as a closed system. This therefore brings us to the problem of defining Hinduism which is by no means an easy task as there is no agreement on any singular definition. Pre-modern India had more contacts with her neighbours and thus central Asia and south East Asia emerge as some of the main regions where Indian influence is seen in many aspects of life. Even to a casual observer of both central Asia and South East Asia we see that there striking Indian influences in culture, religion and other aspects of life. All of them are not part of the textual literature that has become very nationalistic in the recent past and this tends to also dismiss the earlier writings as western Eurocentric. It is true that there is a great element of eurocentricism in the earlier writings but one point that needs to be highlighted is that these earlier writings also faithfully portrayed many aspects like iconography etc. in a very descriptive manner that focused on the measurements, likeness, colour and other associated characteristics of the statues. Such trends are clearly visible in the writings of Jas Burgess,E.B Havell etc. who were influenced by the dominant paradigm in contemporary Europe of the 1850‟s where the duty of the historian was to just record. Such an approach was informed by the writings of the German philosopher Leopold Von Ranke. Though there are certain value judgments at the end of the chapter, the main narrative is a dry as dust and it is easy to decipher the characteristics or reconstruct the iconographic programme in any shrine and by extension the religious practices. In the modern period , where the dominant forms of anti-colonial struggles led to a writing of nationalist history succeeded by Marxist influenced social histories in many parts of Asia, the identification of the national boundaries and national cultures also extended to religions and many aspects were either muted or totally obliterated in history writing to present a homogenous picture. Thus, we have a picture of Hinduism and Buddhism that fits in with the national narratives. Such a collapse of categories is there in the borderland of India where the cultural boundaries are not clearly marked as also h religious boundaries. One single example that illustrates this assertion is the portrayal of Sri Lanka as a Sinhala Buddhist region with the Tamil regions of Sri Lanka marked off as separate entity and both being largely exclusive. In the Buddhist temples of Sri Lanka, one finds firstly the statue of Ganesha and later the images of Karthikeya and also the god Shani or Saturn. This image of a Buddhist monastery sharply contrasts with the highly buddhistic space of a Sinhala Buddhist temple where non-Buddhist elements are not found.